STRATEGI PEMASARAN MAKANAN TRADISIONAL ASAM PEDAS IKAN PATIN KHAS PEKANBARU PADA RESTORAN PONDOK PATIN HM. YUNUS - Dwi Yanda Gunawan; Andri Sulistyani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Due of the Pondok Patin HM. Yunus Restaurant in Pekanbaru that capture this opportunity is Pondok Patin HM. Yunus Restaurant. The aims of this sturly are identify the implemented marketing strategy, idendify the determinals of marketing strategy forfulation, formulated new marketing strategy. Pondok Patin HM. Yunus Restaurant uses 4 p marketing mix : 1) Product 2) Price 3) Promotion 4) Place. Pondok Patin HM. Yunus restaurant was one of restaurant who providing the signature main course of Pekanbaru city. This study aims to describe how their marketing strategy working regarding the tradisional signature main course of Pekanbaru called “Asam Pedas Ikan Patin”. The Data were obtained through direct interview with the owner of Pondok Patin HM. Yunus restaurant as well as direct observation and documentation: The result obtained from this study that Pondok Patin HM. Yunus restaurant has a great marketing strategy that has a good effect on their sales revenue.Keyword: Marketing Mix, Marketing Strategy, Traditional cuisine , Restaurant